Krótko- i długofalowe korzyści wczesnej opieki nad dzieckiem i edukacji - Brzezińska, Anna Izabela; Czub, Magdalena; Czub, Tomasz (My University, 2012)
The Western societies idea of need to invest in early care and education of the youngest citizens become more and more prevalent and is supported by scientific research. The condition of the young people in our country, indicates the need to promote the idea also in Poland. The paper contains an analysis of the research on the effectiveness of early educational interventions. Research confirms the positive impact of early educational effects on the functioning in the school and the duration of the education, as well as on social functioning measured by the level of employment, income and assets. The benefits of early childhood education are also visible in the lower criminality. Conducted research also indicates that from the point of view of state economics, early care and education is beneficial.

Coraz szerzej rozpowszechniony w społeczeństwach zachodnich pogląd mówiący o konieczności inwestowania w edukację i opiekę nad najmłodszymi obywatelami znajduje potwierdzenie w badaniach naukowych i staje się, zważywszy na kondycję młodych ludzi w naszym kraju, konieczny do upowszechnienia także w Polsce. Artykuł zawiera analizę badań dotyczących efektywności wczesnych oddziaływań edukacyjnych. Badania potwierdzają pozytywny wpływ wczesnych oddziaływań edukacyjnych zarówno na funkcjonowanie w szkole i czas trwania nauki, jak i na funkcjonowanie społeczne mierzone poziomem zatrudnienia, dochodów i stanu posiadania. Korzyści z wczesnej edukacji widoczne są także w zakresie niższej przestępczości. Prowadzone badania wskazują również, iż z punktu widzenia ekonomii państw, wczesna opieka i edukacja przynosi wymierne korzyści.
Short- and longterm benefits from early care and education of children
Keywords: wczesna opieka i edukacja; early childhood education and care; efektywność; effectiveness; korzyści długofalowe; long-term benefits; funkcjonowanie szkolne; school functioning; funkcjonowanie społeczne; social functioning; zyski ekonomiczne; economic benefits